(3GdJShjb GdGdcJQhfj (B/s - (3GdWGFj, jhSa MLje SdWGfs; (3OHGS GdYHGOj, gGTe ahRj s ((3YeGf(B: s (3eDSSI GdhQGb ddfTQ hGdJhRjY(B, s, 2009)
(3GdJShjb GdJbdjOj , JcfhdhLjG GdeYdheGJ h GdGJUGdGJ GdGfJQfjJ , GdeONd aj OQGSI GdJShjb GdGdcJQhfj, GdCShGb GdGdcJQhfjI h GdCYeGd GdGdcJQhfjI, CHYGO GdJShjb GdGdcJQhfj h CSGSjGJg, GdJShjb GdGdcJQhfj ef GdCYeGd Edi GdCYeGd h ef GdGYeGd Gdi GdRHhfs
(3bGFeI GdLOGhd U(B.13(3;bGFeI GdGTcGd U(B.15s
Keywords: (3GdJShjbs; (3GdJShjb GdGdcJQhfjs; (3JcfhdhLjG GdeYdheGJs